Nutritional composition and quality of African catfish (Clarias gariepinus) fed with Melaleuca cajuputi leaves extracts as a natural feed additive - Karim N.U.,; Mohd Khairul Sahimi M.B.,; Hassan M., (Penerbit Universiti Kebangsaan Malaysia, 2017)
African catfish, Clarias gariepinus were treated as; controls (fed with commercial feed); T1, (fed with 5 mg kg-1 Melaleuca leaves extract formulated in commercial feed); and T2 (fed with 10 mg kg-1 Melaleuca leaves extract formulated in commercial feed) and fed twice daily for 21 days. The effects of the treatments on nutritional composition, microbiological and physicochemical quality of the catfish were analysed. The nutritional composition of the catfish fed with Melaleuca leaves extract formulated in commercial feed were not significantly modified (p>0.05). However, lipid and fibre content in T2 catfish showed a significantly (p<0.05) higher composition compared to the controls. The total bacteria load of T2 were successfully reduced (p<0.05) compared to T1 and the controls. Water holding capacity (WHC) of T2 catfish were recorded higher (77.93±6.95 %) but not significantly (p>0.05) different to the T1 and controls. pH value in all samples were recorded at range of 5.2-5.6. Meanwhile the colour value (L*, a* and b*) were not significantly (p>0.05) different in all samples. Feed additive of 10 mg kg-1 Melaleuca leaves extract are potential invention of aquafeed industry to be applied in aquaculture practice as it offers a good microbiological and physicochemical quality to cultured African catfish.